Ag-NPs/MWCNT composite-modified silver-epoxy paste with improved thermal conductivity. Issue 36 (2nd July 2019) - Li, Yanchao; Gan, Guoyou; Huang, Yukuan; Yu, Xianglei; Cheng, Junhua; Liu, Chengbin
Abstract : Heat dissipation is a critical issue in high-performance electronics, which needs to be solved, and an electronic paste is a good choice to solve this issue. Abstract : Heat dissipation is a critical issue in high-performance electronics, which needs to be solved, and an electronic paste is a good choice to solve this issue. In this paper, silver nanoparticles/multi-walled carbon nanotube (Ag-NPs/MWCNT) composites were prepared by the chemical process for the modification of electronic pastes. The micromorphology and spectral analysis of the as-prepared Ag-NPs/MWCNT composites indicated that Ag-NPs were uniformly distributed on the MWCNT surfaces with high distribution densities; the average size of Ag-NPs was estimated to be 8.29 nm. The as-obtained Ag-NPs/MWCNT composites were then added to a silver-epoxy paste. Field emission scanning electron microscopy (FESEM), thermogravimetry (TG) and thermal conductivity analyses suggested the incorporation of Ag-NPs/MWCNT composites in the silver-epoxy paste; Ag flakes were better connected by Ag-NPs/MWCNTs, which improved the thermal conductivity of the paste from 0.73 to 0.96 W m −1 K −1 . However, more weight loss was observed when Ag-NPs/MWCNTs were incorporated in the silver-epoxy paste. Overall, the addition of Ag-NPs/MWCNTs into the silver-epoxy paste increased the thermal conductivity, which can be applied to high-performance electronics.